[CoII(BPyPy2COH)(OH2)2]2+: A Catalytic Pourbaix Diagram and AIMD Simulations on Four Key Intermediates - Roger Alberto; Marcella Iannuzzi; Yeliz Gurdal; Benjamin Probst (CHIMIA, 2019)
Proton reduction by [CoII(BPyPy2COH)(OH2)2]2+ (BPyPy2COH = [2,2'-bipyridin]-6-yl-di[pyridin-2-yl]methanol) proceeds through two distinct, pH-dependent pathways involving proton-coupled electron transfer (PCET), reduction and protonation steps. In this account we give an overview of the key mechanistic aspects in aqueous solution from pH 3 to 10, based on electrochemical data, time-resolved spectroscopy and ab initio molecular dynamics simulations of the key catalytic intermediates. In the acidic pH branch, a PCET to give a CoIII hydride is followed by a reduction and a protonation step, to close the catalytic cycle. At elevated pH, a reduction to CoI is observed, followed by a PCET to a CoII hydride, and the catalytic cycle is closed by a slow protonation step. In our simulation, both CoI and CoII–H feature a strong interaction with the surrounding solvent via hydrogen bonding, which is expected to foster the following catalytic step.